Design, Modeling and Motion Simulation of a Setback Arming Mechanism under Weak Acting Forces. Issue 1 (1st April 2022) - Lv, Bing; Wang, Dongya; Zhang, Zhenze; Sui, Li
Abstract: A parallel two-degree-of-freedom (two-DOF) setback arming mechanism was designed in this study according to acceleration signal characteristics of weak launch and service conditions. A model of an inertia switch with a low g-feature was designed to be used in the electromechanical fuze of the proposed mechanism. Simulations were conducted to analyze the motion characteristics of the inertia switch that was based on the parallel two-DOF spring-mass system under the launch overload and the service dropping overload. The reliability and safety of the inertia switch were validated.